2009
DOI: 10.4076/1752-1947-3-7291
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to sonographic examination in a patient with a calf muscle tear: a case report

Abstract: IntroductionRupture of the distal musculotendinous junction of the medial head of the gastrocnemius, also known as "tennis leg", can be readily examined using a soft tissue ultrasound. Loss of muscle fiber continuity and the occurrence of bloody fluid accumulation can be observed using ultrasound with the patient in the prone position; however, some cases may have normal ultrasound findings in this conventional position. We report a case of a middle-aged man with tennis leg. Ultrasound examination had normal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…One might consider a diagnosis of a rupture of the distal musculotendinous junction of the medial head of the gastrocnemius muscle (tennis leg). This condition is often seen in athletes performing sudden acceleration and deceleration manoeuvres [ 10 ]. The patient denied any history of trauma, and the physical examination revealed localised pain at the medial aspect of the upper left leg.…”
Section: Case Presentationmentioning
confidence: 99%
“…One might consider a diagnosis of a rupture of the distal musculotendinous junction of the medial head of the gastrocnemius muscle (tennis leg). This condition is often seen in athletes performing sudden acceleration and deceleration manoeuvres [ 10 ]. The patient denied any history of trauma, and the physical examination revealed localised pain at the medial aspect of the upper left leg.…”
Section: Case Presentationmentioning
confidence: 99%
“…Studies utilizing MRI, sonography, or surgical exploration show that plantaris injuries may occur in isolation or concomitantly with tears of the gastrocnemius, soleus, or popliteus, 4,7,15,22,27,37,63 but prolific edema can make the precise identification of the involved structures difficult. Magnetic resonance imaging studies suggest that the diagnosis of plantaris strain is appropriate when fluid is observed with a strong clinical suspicion, even when no tear is initially seen.…”
Section: Imagingmentioning
confidence: 99%
“…Nonsurgical treatment is typically administered for 3 to 16 weeks, particularly when there is involvement of the gastrocsoleus complex. 7,24,25 While immobilization is indicated during the acute phase of muscle healing due to histological factors such as capillary growth, granulation tissue formation, muscle fiber regeneration, and biomechanical tensile strength development, these factors have more precedence when healing, repair, and tissue regeneration are the goals. 30,38,39 In this case, immobilization, protected weight bearing, and edema-control strategies were implemented, with the aim to improve function by decreasing pain, inflammation, and muscle soreness; however, as the likelihood of an isolated plantaris rupture increased and the suspicion of a medial gastrocsoleus strain diminished, it was recognized that rehabilitation should focus on treating the objective clinical symptoms and on functional ability, because healing of the tendon was not the aim.…”
Section: Rehabilitation and Return To Playmentioning
confidence: 99%
“…It virtually excluded epilepsy as there is no improvement of seizures even after combination anticonvulsant therapy. Recently it has been demonstrated that long-term anticonvulsant therapy, particularly when more than one drug is used, can precipitate hypocalcaemia 11 .…”
Section: Mechanism Of Development Of Calcification Is Unknownmentioning
confidence: 99%